Know‐how transfer: the role of social, economic/competitive, and firm boundary factors - Kachra, Ariff; White, Roderick E. (Strategic Management Journal, 2008)
Abstract Using policy capture methodology, this study examines the effect of different contextual cues upon the know‐how transfer efforts reported by 79 biotechnology R&D scientists. Theoretically, these different cues are believed to affect the scientists' expectation of reciprocity, and thus their know‐how transfer behavior. Three types of contextual cues between the know‐how source and recipient were studied: competitiveness, social relationship, and within or across firm boundaries. We find these cues are associated, in the expected directions, with know‐how transfer effort. The findings support a general theory of reciprocity whereby social, competitive, and firm boundary cues have a summative effect upon the expectation of reciprocity and know‐how transfer. This is the first study to examine how these cues taken together influence the know‐how transfer decision. Copyright © 2008 John Wiley & Sons, Ltd.